Enrollee mix, treatment intensity, and cost in competing indemnity and HMO plans - Altman, Daniel 1974-; Cutler, David M. 1965-; Zeckhauser, Richard 1940- (National Bureau of Economic Research, 2000)
We examine why managed care plans are less expensive than traditional indemnity insurance plans. Our database consists of the insurance experiences of over 200,000 state and local employees in Massachusetts and their families, who are insured in a single pool. Within this group, average HMO costs are 40 percent below those of the indemnity plan. We evaluate cost differences for 8 conditions representing over 10 percent of total health expenditures. They are: heart attacks, cancers (breast, cervical, colon, prostate), diabetes (type I and II), and live births. For each condition, we identify the portions of the cost differential arising from differences in treatment intensity, enrollee mix, and prices paid for the same treatment. Surprisingly, treatment intensity differs hardly at all between the HMOs and the indemnity plan. That is, relative to their fee-for-service competitor, HMOs do not curb the use of expensive treatments. Across the 8 conditions, roughly half of the HMO cost savings is due to the lower incidence of the diseases in the HMOs. Virtually all of the remaining savings come because HMOs pay lower prices for the same treatment.
Keywords: Health insurance -- Massachusetts -- Costs; Health maintenance organizations -- Massachusetts -- Costs